2012
DOI: 10.1007/8904_2012_170
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Efficacy of Magnesium Valproate in Succinic Semialdehyde Dehydrogenase Deficiency

Abstract: Succinic semialdehyde dehydrogenase deficiency (SSADHD), a disorder of g-aminobutyric acid (GABA) metabolism, manifests typically as a nonprogressive neurodevelopmental disorder with cognitive deficiency, neuropsychiatric morbidity and epilepsy. Therapy targets symptomatic seizures and neurobehavioral disturbances. We report an adolescent female with SSADHD whose unresponsiveness to a broad spectrum of antiepileptics was circumvented with magnesium valproate (MgVPA). Epilepsy remains well controlled in our pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Several reports of EEG in SSADH-deficient patients have revealed slowing in both hemispheres and spike-wave discharges (Vanadia et al, in press), an observation consistent with the effect of GHB on EEG (Snead 1978; 2000; Snead and Gibson 2005). As well, a consistent finding in patients has been hyperintensity on the T1-weighted MRI images in the globus pallidi bilaterally (Pearl et al 2009a; Yalcinkaya et al 2000; Ziyeh et al 2002).…”
Section: Treatment Strategies For Ssadh Deficiencysupporting
confidence: 70%
“…Several reports of EEG in SSADH-deficient patients have revealed slowing in both hemispheres and spike-wave discharges (Vanadia et al, in press), an observation consistent with the effect of GHB on EEG (Snead 1978; 2000; Snead and Gibson 2005). As well, a consistent finding in patients has been hyperintensity on the T1-weighted MRI images in the globus pallidi bilaterally (Pearl et al 2009a; Yalcinkaya et al 2000; Ziyeh et al 2002).…”
Section: Treatment Strategies For Ssadh Deficiencysupporting
confidence: 70%
“…Characterization of the epileptic phenotype in individuals with SSADH deficiency guides the use of antiepileptic drugs or agents used for seizures in general. Valproate is not used as a first‐line therapy because of inhibition of any residual enzymatic activity, although magnesium valproate treatment was shown to successfully control refractory epilepsy in an SSADH‐deficient individual, and this was associated with improved behavior and EEG findings . Reasonable seizure control was observed in individuals with SSADH deficiency using lamotrigine and carbamazepine.…”
Section: Discussionmentioning
confidence: 99%
“…A recent case report has identified magnesium valproate as an agent effective in ameliorating behavioral problems and refractory epilepsy (Vanadia et al 2013). This was an unexpected finding since earlier observations by Simler and colleagues (1981) had revealed that valproate is an inhibitor of SSADH.…”
Section: Treatment Of Ssadhdmentioning
confidence: 99%